Multicultural Counseling-a Review of the Literature: Findings and Recommendations - Novianti, Williya (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
Individual behavior is a manifestation of the culture in which his lives. Human interaction with their environment as well as all kinds of experineces they get from that interaction will drive someone behavior. Behavior is also driven, in part, by thoughts and feelings, which provide insight into individual psyche, revealing such things as attitudes and values. Behavior diversity is a manifestation of different cultures in which people live. so that two people who come from different cultures may show different knowledge, attitudes and behaviors. Cultural diversity is also triggered by globalization where interactions between people from various nations make their respective cultures mingle and even influence each other. In societies, cultural diversity benefits everyone both in professional and educational environments. It paves the way to more empathy and compassion, deepened learning, better problem solving as well as approaches the world from various perspectives. In the context of schools where students are increasingly diverse, multicultural education becomes important to teach so that students' cultural empathy increases and can minimize conflicts between students caused by cultural differences.